Fracture-initiation pressure analysis of horizontal well in anisotropic formations. (6th November 2019) - Ma, Tianshou; Liu, Yang; Chen, Ping; Wu, Bisheng
Lost circulation is a classic wellbore instability problem encountered during drilling. To minimise or avoid lost circulation, preventing the initiation of fracture is the best measure. However, because rocks are naturally anisotropic, the classic fracture pressure model is not applicable for anisotropic formations. Some researchers therefore investigated the influence of transverse isotropic material parameters, but they ignored the influence of anisotropic tensile strength. The present work proposes a novel fracture-initiation pressure model of a horizontal well to investigate the influence of anisotropy on fracture-initiation pressure. Laboratory hydraulic fracturing testing verified the present method. The results indicated that anisotropic modulus and tensile strength have distinct influences on fracture-initiation pressure. Fracture-initiation pressure declines obviously under the influence of anisotropic modulus and anisotropic tensile strength, thus, the anisotropy of modulus and tensile strength cannot be ignored. The present model provides more accurate predictions of fracture-initiation pressure for horizontal wells in anisotropic formations. [Received: July 26, 2017; Accepted: December 19, 2017]